Graphene quantum dots prepared from dried lemon leaves and microcrystalline mosaic structure. (17th May 2021) - Kir, Şifa; Dehri, İlyas and Önal, Yunus and Esen, Ramazan
Abstract : There are the smallest structural units (carbon and/or quantum dots) in the structure of living plants. This carbon and/or quantum dots are stem cells of plants. Abstract: The aim of this study is to obtain graphene quantum dots (GQDs) by using Citrus limonum leaves grown in Adana Province, Mediterranean region. Thus, dried Citrus limonum leaves were subjected to carbonization at temperatures of 200, 275, 350, 425 and 500°C and 90, 180, and 270 min respectively at each temperature. Characterization of the material obtained at the end of the process was determined by using X‐ray diffraction (XRD), Fourier‐transform infrared (FT‐IR), fluorescence spectroscopy, elemental analyzer, scanning electron microscopy (SEM), ultraviolet (UV)‐visible, UV‐A and UV‐C lamps. It was determined that the samples obtained in the carbonization process carried out at 350 and 425°C for 3 h made blue colored fluorescence. The results of the experiments completed for characterization analysis verified the GQDs and mosaic crystal structure compared to the literature. It was observed that the GQDs obtained at 350°C for 3 h had maximum fluorescence properties. Radical changes at the sample matrix was observed when carbonization temperature changed from 350°C to 425°C.